Phenotypic convergence in genetically distinct lineages of a Rhinolophus species complex (Mammalia, Chiroptera). - David S Jacobs (Public Library of Science (PLoS), 2013)
Phenotypes of distantly related species may converge through adaptation to similar habitats and/or because they share biological constraints that limit the phenotypic variants produced. A common theme in bats is the sympatric occurrence of cryptic species that are convergent in morphology but divergent in echolocation frequency, suggesting that echolocation may facilitate niche partitioning, reducing competition. If so, allopatric populations freed from competition, could converge in both morphology and echolocation provided they occupy similar niches or share biological constraints. We investigated the evolutionary history of a widely distributed African horseshoe bat, Rhinolophus darlingi, in the context of phenotypic convergence. We used phylogenetic inference to identify and date lineage divergence together with phenotypic comparisons and ecological niche modelling to identify morphological and geographical correlates of those lineages. Our results indicate that R. darlingi is paraphyletic, the eastern and western parts of its distribution forming two distinct non-sister lineages that diverged ~9.7 Mya. We retain R. darlingi for the eastern lineage and argue that the western lineage, currently the sub-species R. d. damarensis, should be elevated to full species status. R. damarensis comprises two lineages that diverged ~5 Mya. Our findings concur with patterns of divergence of other co-distributed taxa which are associated with increased regional aridification between 7-5 Mya suggesting possible vicariant evolution. The morphology and echolocation calls of R. darlingi and R. damarensis are convergent despite occupying different biomes. This suggests that adaptation to similar habitats is not responsible for the convergence. Furthermore, R. darlingi forms part of a clade comprising species that are bigger and echolocate at lower frequencies than R. darlingi, suggesting that biological constraints are unlikely to have influenced the convergence. Instead, the striking similarity in morphology and sensory biology are probably the result of neutral evolutionary processes, resulting in the independent evolution of similar phenotypes.